An approach for assessing cumulative effects in a model river the Athabasca River basin - Squires, Allison Jane; Westbrook, Cherie J.; Dube, Monique G. (Integrated Environmental Assessments and Management, 2010)
Novel approaches addressing aquatic cumulative effects over broad temporal and spatial scales are required to track changes and assist with sustainable watershed management. Cumulative effects assessment (CEA) requires the assessment of changes due to multiple stressors both spatially and temporally. The province of Alberta, Canada, is currently experiencing significant economic growth as well as increasing awareness of water dependencies. There has been an increasing level of industrial, urban, and other land-use related development (pulp and paper mills, oil sands developments, agriculture, and urban development) within the Athabasca River basin. Much of the historical water quantity and quality data for this basin have not been integrated or analyzed from headwaters to mouth, which affects development of a holistic, watershed-scale CEA. The main objectives of this study were 1) to quantify spatial and temporal changes in water quantity and quality over the entire Athabasca River mainstem across historical (1966–1976) and current day (1996–2006) time periods and 2) to evaluate the significance of any changes relative to existing benchmarks (e.g., water quality guidelines). Data were collected from several federal, provincial, and nongovernment sources. A 14% to 30% decrease in discharge was observed during the low flow period in the second time period in the lower 3 river reaches with the greatest decrease occurring at the mouth of the river. Dissolved Na, sulfate, chloride, and total P concentrations in the second time period were greater than, and in some cases double, the 90th percentiles calculated from the first time period in the lower part of the river. Our results show that significant changes have occurred in both water quantity and quality between the historical and current day Athabasca River basin. It is known that, in addition to climatic changes, rivers which undergo increased agricultural, urban, and industrial development can experience significant changes in water quantity and quality due to increased water use, discharge of effluents, and surface run-off. Using the results from this study, we can begin to quantify dominant natural and man-made stressors affecting the Athabasca River basin as well as place the magnitude of any local changes into an appropriate context relative to trends in temporal and spatial variability.
Keywords: aquatic environment; assessment; Athabasca River; chemistry; effects; hydrology; impact; tributaries; UofS